The "magnet effect" - a powerful source of L1 dialect interference in the pronunciation of English as a foreign language - Jurančič, Klementina (ELOPE (Ljubljana), 2014)
Wieden and Nemser (1991) carried out a study investigating the development of pronunciation of English as a foreign language in Austria. One of the main issues in this research was L1 dialect interference. Individual studies have proven that the pronunciation of a second (L2) or foreign language (FL) is not influenced only by the standard variety of the first language (L1), but also by the L1 dialect of the speaker's place of origin (Karpf et al. 1980). Wieden and Nemser's study wished to prove this on a larger scale. A similar study was carried out also for Slovenia (Jurančič Petek 2007). Contrastive analysis (CA) of the Slovene Standard pronunciation and English was performed as well as that of the sound systems of individual Slovene dialects and the English one. Error analysis (EA) of the obtained results showed that L1 dialect interference did not occur in the instances predicted by contrastive analysis; however the study in itself did prove the existence of such influence ("magnet effect" in vowels).
Keywords: angleščina; dialect; English; izgovorjava angleščine; magnetni učinek; monoftongi; narečja; vpliv materinščine